Comparison of in vitro dentinal tubule occluding efficacy of two different methods using a nano-scaled bioactive glass-containing desensitising agent. (May 2017) - Ma, Qian; Wang, Tianda; Meng, Qingfei; Xu, Xiao; Wu, Huaying; Xu, Dongjing; Chen, Yaming
Abstract: Objective: This study aimed to compare the in vitro dentinal tubule occluding efficacy of two different methods using a nano-scaled bioactive glass (BG)-containing desensitising agent. Methods: Citric acid treated dentine discs were randomly divided into 7 groups (n = 8). Group A1, A2 and A3: dentine discs coated with BG desensitising paste; Group B1, B2 and B3: dentine discs coated with BG desensitising paste and covered with matched transparent trays; and control group (Group C): dentine discs treated with deionised water. Field Emission Scanning Electron Microscopy (FE-SEM) was used to capture topographical images of each dentine discs after they were immersed in artificial saliva for corresponding treatment time and dentinal tubules exposure rates were thus measured. Elemental compositions of dentine discs were identified using Energy-Dispersive X-ray Spectroscopy (EDX). Results: FE-SEM revealed better tubule occluding effects in Group B. Dentinal tubules in Group B3 were totally occluded with continuous homogeneous minerals to a depth of 20.6-24.7 μm. Dentinal tubule exposure rates in Group B1, Group B2 and Group B3 were lower than that in Group A1, Group A2 and Group A3. EDX indicated that occluding deposits observed in each group were calcium-deficient hydroxyapatite. Conclusions: The application of transparent trays in combination with nano-scaled BG-containing desensitising paste could increase the dentinal tubule occluding effectiveness of the latter one and shorten the treatment time. Clinical relevance: Transparent trays could be used in combination with BGs-containing desensitising paste as the containers of the latter one in order to increase the dentinal tubule occluding effectiveness. This could lead to the development of a new therapeutic technique for treating dentine hypersensitivity.